Законотворча діяльність у сфері архівної справи Польщі у повоєнний період (1950-ті рр.) - Мельник, Р. (Архіви України, 2009)
The article explores law-making activity in the sphere of Polish archives in the first post-war years. The author singles out key factors which determined changes in the archive legislation of the given period. The article reflects major stages of preparation and implementation of these changes to the regulatory system of this sphere. In the 1950-ies the system was formed by three acts: the State Archives Decree, the Resolution of the Head of the Cabinet Council on the Archive Network, and the Instruction of the Cabinet Council on the State Archive Fund. The main part of the paper is devoted to analysis and characteristics of the above-mentioned acts. In addition, the author investigates changes caused by these acts in archive organization and activity of Polish archives, reveals their role and meaning for the development of Polish archives.